Induction of hepatic aminolevulinate acid synthetase activity by isoflurane in a genetic model for erythropoietic protoporphyria - Buzaleh, A M; Morán-Jiménez, M J; Garcia-Bravo, M; Sampedro, A; Batlle, A M Del C; Enriquez De Salamanca, R; Fontanellas, A (Cellular and Molecular Biology, 2015)
Erythropoietic Protoporphyria (EPP) is an inherited deficiency of ferrochelatase, the last enzyme of the heme pathway. Under general anaesthesia, some patients develop neurological dysfunction suggesting upregulation in heme biosynthesis similar to that described for acute porphyrias after xenobiotic administration. Our aim has been to evaluate whether Isoflurane induces alterations in the heme pathway in a mouse model for EPP. Administration of Isoflurane (a single dose of 2 ml/kg, i.p) to wild-type (+/+), heterozygous (+/Fechm1Pas) and homozygous (Fechm1Pas/Fechm1Pas) mice, was evaluated by measuring the activity of ï¤-Aminolevulinic acid synthetase (ALA-S) and Porphobilinogen-deaminase (PBG-D) in different tissues, as well as Heme oxygenase (HO), cytochrome P-450, CYP2E1 and glutathione levels in liver. Porphyrin precursors were measured in 24h-urine samples. Fechm1Pas/Fechm1Pas mice receiving anaesthesia show enhanced ALA-S and CYP2E1 activities in the liver and increased urinary excretion of porphyrin precursors. No alterations were found in either PBG-D or HO activities. Diminished glutathione levels suggest that anaesthesia may produce oxidative stress in these animals. In conclusion, Isoflurane induces ALA-S activity and increased excretion of porphyrin precursors in EPP mice. These findings appear to confirm our previous hypothesis and indicate that Isoflurane may be an unsafe anaesthetic not only for patients with acute porphyrias but also for individuals with non acute porphyrias.